“ La Limougère ” : un établissement rural de la fin de La Tène à Fondettes (Indre-et-Loire) - Matthieu Gaultier (Revue Archéologique du Centre de la France)
The archeological survey realised before the construction of the Tours ring road (north-west section) have revealed the “Limougère” archaeological site. Excavated in 2006, it is located in Fondettes (Indre-et-Loire). This is a little farm occupied from the end of the La Tène C period to the end of the last century BC. The excavation produced only a few structures: ditches that determined the limits of the enclosure, two little barns based on posts, a well… However we can suggest a hypothesis for the farm's spatial organisation based on the analysis of the spatial dispersion of the artefacts. This site belongs to the Turons corpus of rural settlements organized around an excavated enclosure. Most of these farms appear at the end of the La Tène C period and develop during the last century BC.